The Effectiveness of Science Learning Based on Volcanic Activity Data in Enhancing Students’ Disaster Literacy in North Maluku - Hi. Ismail, Agus R.; Lestari , Fitri Ayu; Faradina; M. Yasin, Fazrul (SEARCH: Science Education Research Journal, 2026)
This study aims to analyze the effectiveness of science learning based on volcanic activity data in improving students’ disaster literacy in North Maluku. The study employed a quasi-experimental method using a pretest–posttest control group design. The participants were Grade 10 senior high school students, divided into an experimental group and a control group. The experimental group was taught using authentic data on volcanic activity, such as data from Mount Ibu and Mount Dukono, while the control group received conventional instruction. The results revealed a significant improvement in disaster literacy among students in the experimental group, with an N-gain score of 0.68 (moderate–high category), compared to 0.32 (low–moderate category) in the control group. The results of the t-test showed a significance value of 0.001 (p < 0.05), indicating a statistically significant difference between the two groups. Therefore, science learning based on volcanic activity data is effective in enhancing students’ disaster literacy.